Bioconvection of oxytactic microorganisms with nano-encapsulated phase change materials in an omega-shaped porous enclosure - Shafqat Hussain (3922565) (2022)
In this paper, the bioconvection of oxytactic microorganisms with nano-encapsulated phase change materials (NEPCMs) in an omega-shaped porous enclosure is considered and analyzed. The main focus of this study is to examine the flow of a suspension containing NEPCMs together with bioconvection of oxytactic microorganisms in a novel type of cavity, namely, an omega-shaped porous enclosure. The thermophysical properties of the nanoparticles are assumed to be dependent on the properties of the core and shell. The Galerkin-based finite element technique (GFEM) is utilized to perform the simulations of the proposed configuration. Adaptive Newton's method is invoked to treat the discrete algebraic systems. The implemented FEM code has been validated against the experimental and numerical published available data in the literature. The impact of various controlling parameters on the flow and heat transfer characteristics is examined and discussed. The major findings of the study revealed that the fusion temperature controls the intensity and position of the melting zone towards the heated irregular boundary within an omega-shaped enclosure. Moreover, the Oxygen and Microorganisms isoconcentration is enhanced as the bioconvection Rayleigh number grows. Other Information Published in: Journal of Energy Storage License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.est.2022.105872